Antimicrobial Activity of Lactic Acid Bacteria Found in Dadiah on Disease-Causing Skin Infections (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dadiah is a fermented food made from buffalo milk containing lactic acid bacteria (LAB). The potentialof LAB as an antimicrobial organism is expected to inhibit or kill pathogens, especially those causinginflammations in the skin. Dadiah used in this study was obtained from the Lintau area of Tanah DatarDistrict, West Sumatra, Indonesia. LAB isolation and identification involved the use of MRS Broth(MERCR) and MRS Agar (MERCK) media and the pathogenic bacteria used include Staphylococcusaureus, Propionibacterium acnes, Acinetobacter Baumannii, Klebsiella pneumonia, and Pseudomonasaeruginosa. The results of this study obtained a total LAB of 7x1011 CFU / g and showed the highestantimicrobial activity in the Staphylococcus aureus with a14.53 mm clear zone and 13.18 mm bacteria inthe Pseudomonas aeruginosa test bacteria.
Keywords: Antimicrobial dadiah, lactic acid bacteria, skin diseases